Discrete and continuous nonlinear Schrödinger systems - Ablowitz, Mark J. (London Mathematical Society lecture note series ;, 2004)
In this book, the detailed mathematical analysis of the scattering theory is presented, soliton solutions are obtained and soliton interactions, both scalar and vector, are analyzed. Many details presented, including aspects of the scattering theory, solution methodology, soliton solutions and vector soliton interactions are not available in the previously-published literature.